A New Look to Nuclear Data. (3rd July 2017) - McCutchan, E. A.; Brown, D. A.; Sonzogni, A. A.
Abstract : Databases of evaluated nuclear data form a cornerstone on which we build academic nuclear structure physics, reaction physics, astrophysics, and many applied nuclear technologies. In basic research, nuclear data are essential for selecting, designing, and conducting experiments, and for the development and testing of theoretical models to understand the fundamental properties of atomic nuclei. Likewise, the applied fields of nuclear power, homeland security, stockpile stewardship, and nuclear medicine all have deep roots requiring evaluated nuclear data. Each of these fields requires rapid and easy access to up-to-date, comprehensive, and reliable databases. The Department of Energy (DOE)–funded U.S. Nuclear Data Program is a specific and coordinated effort tasked to compile, evaluate, and disseminate nuclear structure and reaction data such that it can be used by the worldwide nuclear physics community.